Decarbamoylation of N-alkoxy-N-(4-dimethylaminopyridin-1-ium-1-ul)urea chlorides in dimethy-lsulfoxide as a route to 1-alkoxyamino-4-dimethyl-aminopyridinium chlorides - Shtamburg, Vasiliy Georgievich; Штамбург, Василь Георгійович; Shtamburg, Victor Vasilievich; Штамбург, Віктор Васильович; Anischenko, Andrey Alexandrovich; Аніщенко, Андрій Олександрович; Kravchenko, Svetlana Vladimirovna; Кравченко, Світлана Володимирівна; Mazepa, Alexander Vladimirovich; Мазепа, Олександр Володимирович; Klots, Evgeniy Alexandrovich; Клоц, Євген Олександрович (Research Centre for Natural Sciences, Hungarian Academy of Sciences, 2018)
Decarbamoylation of N-alkoxy-N-(4-dimethylaminopyridin-1-ium-1-yl)urea chlorides in dimethylsulfoxide takes place with the formation of 1-alkoxyaminopyridinium chlorides. The nature of N-alkoxy substituents has a great influence on decarbamoylation efficiency. Декарбомоілювання хлоридів N-алкокси- N-(4-диметиламіно-піридин-1-іум-1-іл) сечовин відбувається з утворенням 1-алкоксиамінопіридиніум хлоридів. Природа N- алкокси замісників має великий вплив на ефективність декарбомоілювання.
Декарбомоілювання хлоридів N –алкокси- N-(4-диметиламінопіридин-1-іум-1-іл) сечовин у диметилсульф-оксид як шлях до 1-алкоксиаміно-4-диметиламінопіридиніум хлоридів.
http://orcid.org/0000-0001-5384-9559 S. V. Kravchenko
Keywords: N-alkoxy- N-(pyridin-1-ium-1-yl)urea chlorides; N-алкокси- N-(піридин-1-іум-1-іл)сечовин хлориди; decarbamoylation; декарбомоілювання; 1-alkoxyamino-4-dimethylaminopyridinium chlorides; 1-алкоксиаміно-4-диметиламінопіридиній хлориди; structure; структура; O-N-N geminal systems; O-N-N гемінальні системи; dimethylsulfoxide; диметилсульфоксид